2009
DOI: 10.2478/v10096-009-0028-x
|View full text |Cite
|
Sign up to set email alerts
|

Biostratigraphy of the Cretaceous/Tertiary boundary in the Sirwan Valley (Sulaimani Region, Kurdistan, NE Iraq)

Abstract: Abstract:The Cretaceous/Tertiary (K/T) boundary sequence, which crops out in the studied area is located within the High Folded Zone, in the Sirwan Valley, northeastern Iraq. These units mainly consist of flysch and flysch-type successions of thick clastic beds of Tanjero/Kolosh Formations. A detailed lithostratigraphic study is achieved on the outcropping uppermost part of the Upper Cretaceous successions (upper part of Tanjero Formation) and the lowermost part of the Kolosh Formation. On the basis of the ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 27 publications
0
22
0
Order By: Relevance
“…The Maastrichtian-Danian boundary at the El Kef section in Tunisia (Arenillas et al, 2004;Molina et al, 2006Molina et al, , 2009, the tropical and subtropical realm (Berggren and Pearson, 2005;Wade et al, 2011), Gubbio section in Italy (Coccioni and Premoli Silva, 2015;Coccioni et al, 2016), Danial section in the Izeh zone Beiranvand et al, 2014b) and Kabirkuh section in the Lurestan salient (Darvishzad et al, 2007) are conformable, but in Lali (Beiranvand et al, 2014b) and our study area, this boundary is unconformable. In Jordan (Farouk et al, 2014) and most places in Iraq (Sharbazheri et al, 2009), a hiatus occurred at this boundary, while it is conformable in the Sirwan Valley, northeastern Iraq (Sharbazheri et al, 2009) (Fig. 14).…”
Section: Comparison Of Proposed Biozonation With Other Localitiesmentioning
confidence: 90%
“…The Maastrichtian-Danian boundary at the El Kef section in Tunisia (Arenillas et al, 2004;Molina et al, 2006Molina et al, , 2009, the tropical and subtropical realm (Berggren and Pearson, 2005;Wade et al, 2011), Gubbio section in Italy (Coccioni and Premoli Silva, 2015;Coccioni et al, 2016), Danial section in the Izeh zone Beiranvand et al, 2014b) and Kabirkuh section in the Lurestan salient (Darvishzad et al, 2007) are conformable, but in Lali (Beiranvand et al, 2014b) and our study area, this boundary is unconformable. In Jordan (Farouk et al, 2014) and most places in Iraq (Sharbazheri et al, 2009), a hiatus occurred at this boundary, while it is conformable in the Sirwan Valley, northeastern Iraq (Sharbazheri et al, 2009) (Fig. 14).…”
Section: Comparison Of Proposed Biozonation With Other Localitiesmentioning
confidence: 90%
“…Coccioni and Premoli Silva (2015) stated that the zonal marker is very rare and, sporadically, presented through their revision and identification of the CF1 Zone at the classical Tethyan Gubbio section (Italy). Sharbazheri (2008) and Sharbazheri et al (2011) recorded the CF1 Zone in their study of the Cretaceous/Paleogene boundary in Sulaimani area of Kurdistan Region. Salih et al (2013) and Al-Mutwali and Ibrahim (2019) recorded the same zone from Northern and Northeastern Iraq.…”
Section: • Pseudoguembelina Palpebra (Cf2) Interval Zone (Late Late Maastrichtian)mentioning
confidence: 96%
“…Many studies of the uppermost Cretaceous deposits in Iraq and Kurdistan Region suggested that the Cretaceous ends with probably abrupt, erosional, paraunconformity or hiatus among them (Al-Safawee, 1982;Al-Mutwali, 1983;Al-Shaibani and Al-Qayim, 1986;Kassab, 1986;Ghafor, 1988;Al-Qayim and Al-Shaibani, 1995;Al-Omari et al, 1994;Awadh et al, 2008;Al-Hadiedi, 2010;Hammoudi, 2011;Al-Mutwali and Al-Doori, 2012;Al-Wazan, 2013;Al-Mutwali and Ibrahim, 2019;Al-Dulaimi and Abdallah, 2019). In contrast, other foraminiferal biostratigraphic studies have supported the occurrence of complete uppermost Maastrichtian deposits (Sharbazheri et al, 2009 and2011;Salih et al, 2013;Mousa et al, 2020;Al Nuaimy et al, 2020). The current high resolution biostratigraphic study aims to prove the occurrence of complete uppermost Maastrichtian deposits throughout the planktic foraminiferal assemblages and its biozonations for the upper part of the Shiranish Formation, Duhok area, Kurdistan Region, North of Iraq.…”
Section: Introductionmentioning
confidence: 94%
“…Some confusion has arisen on the status of the Kolosh Formation, the only siliciclastic unit of this sequence. Seilacher (1963, in Jassim andGoff 2006) and Jassim and Goff (2006) considered the formation as molasse sediments, whereas Al-Qayim et al (1988), Al-Qayim (1993, 1995a, and Al-Sakry (2006) and part of Sulaimani areas (Sharbazheri et al 2009(Sharbazheri et al , 2011 and with unconformable contacts in other regions (Kassab 1975). On the other hand, the upper contact with the Middle-Upper Eocene rock units is unconformable (Bellen et al 1959).…”
Section: Introductionmentioning
confidence: 95%